Studies on Schismatoglottideae (Araceae) of Borneo LXIV : Another new species for the Schismatoglottis Patentinervia Clade from the Rejang Basin, Sarawak - Sin Yeng, Wong; Aisahtul, Wardi; Peter, C. Boyce (International Aroid Society, 2018)
Schismatoglottis gangsai S. Y. Wong, Aisahtul & P. C. Boyce is described and illustrated from Kapit, C Sarawak, as a new species for the Schismatoglottis Patentinervia Clade and diagnosed against the two morphologically most similar species, S. belonis S. Y. Wong, Aisahtul & P. C. Boyce and S. gephyra P. C. Boyce. An identification key to S. gangsai and its closest congeners of the Rejang Basin is provided. Recognition of S. gangsai takes the Patentinervia Clade to 10 described species, of which 8 have been described since 2000.